2022
DOI: 10.1038/s41396-022-01244-5
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions between predatory protists and pathogen-suppressive bacteria impact plant health

Abstract: Plant health is strongly impacted by beneficial and pathogenic plant microbes, which are themselves structured by resource inputs. Organic fertilizer inputs may thus offer a means of steering soil-borne microbes, thereby affecting plant health. Concurrently, soil microbes are subject to top-down control by predators, particularly protists. However, little is known regarding the impact of microbiome predators on plant health-influencing microbes and the interactive links to plant health. Here, we aimed to decip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 89 publications
3
66
0
Order By: Relevance
“…It is premature to couple the increased activity of members of this predatory protistan order with the strong stimulation of Pseudomonadaceae in this cover crop species. However, a novel study by Guo et al (2022) connected the enrichment of protistan predators with the stimulation of disease-suppressive bacteria belonging to Bacillus spp . in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…It is premature to couple the increased activity of members of this predatory protistan order with the strong stimulation of Pseudomonadaceae in this cover crop species. However, a novel study by Guo et al (2022) connected the enrichment of protistan predators with the stimulation of disease-suppressive bacteria belonging to Bacillus spp . in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the seed‐endophytic bacterium Sphingomonas melonis can be transmitted across generations in disease‐resistant rice seeds and positively affects rice resistance to pathogens by producing anthranilic acid (Matsumoto et al, 2021). Besides bacteria and fungi, accumulating evidence suggests that protists and algae are also important members of the crop microbiome, which can provide protective effect on crop health (Guo et al, 2022; Lee & Ryu, 2021; Xiong et al, 2020). For instance, a recent study showed that protistan predators can strongly enhance banana health and yield by stimulating disease‐suppressive bacteria like Bacillus spp.…”
Section: Diversity and Functions Of Microorganisms In Agroecosystemsmentioning
confidence: 99%
“…For instance, a recent study showed that protistan predators can strongly enhance banana health and yield by stimulating disease‐suppressive bacteria like Bacillus spp. (Guo et al, 2022). Algal species like prokaryotic Anabaena spp.…”
Section: Diversity and Functions Of Microorganisms In Agroecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, legumes such as faba bean and chickpea acidify the rhizosphere by releasing protons and organic acids (Li et al, 2007;Wen et al, 2021), which may increase Fe availability but decrease siderophore production by bacteria. Most microbial siderophores are synthesized by nonribosomal peptide synthetase (NRPS)-dependent pathway (Kadi and Challis, 2009;Verbon et al, 2017), and act as microbicides to suppress plant pathogens (Guo et al, 2022), such as the pyochelin (De Vleesschauwer et al, 2006) and enterochelin (Lambrese et al, 2018). Hence, competition for iron between crop and rhizosphere microbiome may be an important mechanism explaining disease suppression, although other mechanisms such as antibiosis or activation of plant immunity are also involved (Li et al, 2021c).…”
Section: Introductionmentioning
confidence: 99%